Kritik Sosial Dalam Karya Seni - Prima Yustana (Ornamen, 2008)
There are several topics overshadowing an artwork functioning as the means of social critique, perhaps constituting the funny but satire thing, beautiful thing or even the ugly one. All of artworks performed for that purpose will, of course, emerge as something interesting; in addition to that the work assumes a responsibility as the means of evaluating and correcting, however, the more important thing is the meaning of artwork, whether or not the meaning of what attempts to be conveyed by the artist reach the goal and can be understood well so that it will give input into the clumsiness or whether it result in confusion in the interpretation of artwork. This highly depends on each artist individual’ skill and competence in processing idea as well as in manifesting it into his/her work.Keywords: Critique, Art, Communication